POLA OPERASI WADUK BENDO DENGAN MODEL FUZZY STOCHASTIC DYNAMIC PROGRAMMING - Saputra, Anggara Wiyono Wit (Fakultas Teknik, Universitas Brawijaya, 2015)
Abstrak: Pola operasi waduk untuk mendapatkan lepasan waduk yang optimal telah lama diteliti selama bertahun-tahun. Berbagai teknik telah dikembangkan dan diaplikasikan untuk pola operasi waduk dalam hubungannya dengan ketidakpastian akibat sifat stokastik pada tiap objective yang berada dalam operasi waduk serta akibat ketidak tepatan nilai tujuan pada setiap fungsi kegunaan waduk.Model fuzzy stochastic dynamic programming digunakan untuk mengkalkulasi lepasan waduk yang optimal dari operasi waduk multipurposes. Untuk menjabarkan sebuah pola operasi untuk waduk multipurpose maka dibuat sistem pola operasi dengan menggunakan model stokastik dinamik. Pola operasi ini dibuat dengan berdasarkan kepada lepasan waduk optimum untuk setiap operasi waduk yang dihasilkan dari metode fuzzy stochastic dynamic programming. Model fuzzy rule base berdasar pada prinsip â€œIF-THENâ€, dimana â€œIFâ€ adalah sebab dan â€œTHENâ€ adalah fuzzy consequences.Volume tampungan waduk, estimasi inflow, dan kebutuhan digunakan sebagai sebab dan lepasan waduk diambil sebagai fuzzy consequences. Performance indices untuk reliability, repairability, periode kegagalan dan vulnerability digunakan untuk mengevaluasi performa dari tiap Â pola operasi waduk.Kata kunci : Fuzzy Rule Base, Operasi Waduk, Membership FunctionÂ Abstract:Â Reservoir operation to find an optimal release has been researched for many years. Various techniques have been developed and adopted for reservoir operation rule incorporating the uncertainty due to stochastic nature of objectives in the reservoir operation and due to imprecise goal values in the reservoir purposes. The fuzzy stochastic dynamic programming model is used to calculate an optimal release from the operation of multipurpose single reservoir. To derive operation rule for a multipurpose single reservoir a stochastic dynamic model operation rule is constructed. Operation rule are generated based on optimal release for reservoir operation resulted from fuzzy stochastic dynamic programming method. The fuzzy rule base model operates on an â€œIF-THENâ€ principle, where the â€œIFâ€ is a vector of fuzzy explanatory variable or premises and â€œTHENâ€ of fuzzy consequences. The reservoir storage volume, estimated inflows, and demand are used as the premise and release from the reservoir is taken as consequences. Performance indices namely reliability, repairabilitiy, incident period and vulnerability are used to evaluate performance of the reservoir operation rules.Keywords : Fuzzy Rule Base, Reservoir Operation, Membership Function